A multi‐site study of functional outcomes following a themed approach to hand–arm bimanual intensive therapy for children with hemiplegia. (5th March 2013) - Green, Dido; Schertz, Mitchell; Gordon, Andrew M; Moore, Amarlie; Schejter Margalit, Tamara; Farquharson, Yvonne; Ben Bashat, Dafna; Weinstein, Maya; Lin, Jean‐Pierre; Fattal‐Valevski, Aviva
<x xml:space="preserve">Abstract</x> Aim This study investigated the effects of a theme‐based ('magic') variation of the hand–arm bimanual intensive therapy programme, in two different countries, in improving activity performance for children with hemiplegia, including those with severe movement restrictions. Method Twenty‐three children with spastic hemiplegia (13 males, 10 females; mean age 10y 7mo, range 7–15y; Manual Ability Classification System level I, two; level II, 13; level III, eight), participated in one of three, 2‐week, summer camps. A within‐participant experimental design was used with the Assisting Hand Assessment and Children's Hand Experience Questionnaire as primary outcome measures. Evaluations occurred immediately before the first day, on the last day, and 3 months after intervention. Two groups underwent additional assessments 2 weeks before the camp. Results Significant intervention effects were seen on the Assisting Hand Assessment (p=0.002) and on the Children's Hand Experience Questionnaire (p<0.001), the latter maintained at follow‐up. The affected hand was reported to be used in 25% of bimanual activities before the camp, progressing to 93% after camp, and decreasing to 86% at follow‐up. Severity of impairment did not influence progress. Interpretation This themed approach to intensive intervention showed positive results in bimanual use, with improvements in independence sustained at follow‐up. Although children across camps and motor severity made progress, some questions remain about intensity and duration of intervention to optimize longer‐term outcomes.